Productivity of public expenditure - Structural changes for better outcomes - Mathur, B.P. (2005)
The problem of poor delivery of public services has been a cause of worry for the government for more than three decades. For achieving better efficiency of public expenditure, government introduced Performance Budget in 1970s, and Zero Base Budgeting (ZBB) in focuses attention on the fact that poor productivity of public expenditure is inherent in the budgetary and financial management practices and argues for bringing structural changes for better delivery outcomes of public services. -Reproduced.
Keywords: Productivity; Public finance; Public expenditure